Producing IT Professionals with Character: The Role of Islamic Values in Applied Education - Narjul Kirom (Business and Applied Management Journal, 2024)
The purpose of this study is to explore the integration of Islamic personality values in the learning of the Applied Education Program in the Field of Information and Communication Technology (Prodistik) at madrasah aliyah. The background of this research is driven by the need to understand how Islamic values are integrated in the context of applied education in information and communication technology, as well as their impact on the formation of student character. The research method used is field research with a qualitative approach through case studies. Primary data was collected through interviews with managers, instructors, students, and alumni, while secondary data was obtained from relevant literature and documentation studies. The results of the study show that the application of personality values in Islam, such as honesty, discipline, and responsibility, contributes significantly to the formation of students' character. The integration of Islamic values in learning not only improves students' technical competence but also forms an Islamic professional attitude. The application of the principle of trust in information security increases students' awareness of the importance of maintaining confidentiality and data privacy. The implication of this research is the importance of a holistic approach in education that combines technical aspects and spiritual values to form individuals with integrity and character in the face of the complexities of the modern world.